Auxin hormone analysis for clones of immaturity rubber plant - Try Koryati; Luthfi A. M. Siregar (Syiah Kuala University, 2013)
One of the problems of immature rubber plants are non-productive period is too long which is about 5-6 years old. Various efforts have been made to speed up non-productive period, including the application of exogenous growth regulators. This is related to biological natural hormones found in plantduring immature rubber. One of the hormones that affects the auxin hormone . This study aims to analyze content auxin hormone found in some clones and plant age during immature rubber. This research was conducted descriptive / review directly to the field by taking leaf samples at the clones PB 260, PB 340 and RRIM 712 which have been determined. To determine the levels of hormones contained in rubber leaf, leaf samples were analyzed at the Research Center for Biology Indonesian Institute of Sciences in Bogor. Observation auxin hormone levels. The results showed that the type clones and different plant age have different content auxint. The highest content of auxin there at the age of 2 years is the plant on clones PB 260 (116.5 ppm) and RRIM 712 (114.0 ppm).